2009
DOI: 10.1016/j.vaccine.2009.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Activation of toll-like receptor signaling pathway for protection against influenza virus infection

Abstract: This study aims to evaluate the antiviral role of nucleic acid-based agonists for the activation of toll-like receptor (TLR) signaling pathways, and its protective role in respiratory influenza A virus infections. TLR-3 is expressed on myeloid dendritic cells, respiratory epithelium, and macrophages, and appears to play a central role in mediating both the antiviral and inflammatory responses of the innate immunity in combating viral infections. Influenza viruses can effectively inhibit the host's ability to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 9 publications
1
102
0
4
Order By: Relevance
“…(cluster 17). Similar results were observed with regard to Toll-like receptor pathway (clusters 3, 7 and 17), which appears to play a central role in mediating both the antiviral and inflammatory responses of the innate immunity in combating viral infections [39].…”
Section: Innate Immune Responsesupporting
confidence: 78%
“…(cluster 17). Similar results were observed with regard to Toll-like receptor pathway (clusters 3, 7 and 17), which appears to play a central role in mediating both the antiviral and inflammatory responses of the innate immunity in combating viral infections [39].…”
Section: Innate Immune Responsesupporting
confidence: 78%
“…Ideally, the respiratory epithelial cells should also be studied (especially for TLR3 and RLRs);3, 5, 8, 16 however, obtaining such specimens (e.g., with bronchoalveolar lavage ) is generally infeasible in patients with influenza. Studying circulating cells exposed to the pulmonary bed has been shown to provide close estimates 6, 7, 20, 22, 32, 41.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have also revealed an additional cytosolic system of retinoic acid‐inducible gene‐1 (RIG‐1)‐like receptor proteins (RLRs) that detect influenza viral RNAs, contributing to the innate responses 3, 7, 10, 13. Recently, data from animal studies have further shown that targeting the TLRs (with agonists) may rapidly upregulate the innate immunity to provide broad‐range, virus strain non‐specific protection against lethal influenza challenge 4, 11, 14, 15, 16, 17. However, our understanding on TLR's importance in natural influenza is very limited because of lack of clinical data.…”
Section: Introductionmentioning
confidence: 99%
“…Different DC subsets can induce specific TLR pathways following influenza virus infection. For instance, mDCs are activated via TLR3 and TLR9 (41), whereas pDCs are activated via TLR7 (11). The CD8␣ ϩ conventional DC subset specifically initiates CTL immunity in response to influenza virus infection (4).…”
Section: Discussionmentioning
confidence: 99%